Method for producing binder resin for toner
The method addresses the challenge of achieving high abrasion resistance and low VOC emissions in binder resins for toners by using a reaction and condensation process, resulting in a resin that meets environmental standards and improves toner performance.
Patent Information
- Application Number
- JP2021109559
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-30
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2041-06-30
AI Technical Summary
Existing binder resins for toners in electrophotographic systems face challenges in achieving high abrasion resistance while minimizing volatile organic compound (VOC) emissions, which are regulated by stringent environmental standards such as the 'Blue Angel' mark.
A method for producing a binder resin for toners involves a reaction between an alcohol component, a carboxylic acid component, and a modified silicone, followed by steam distillation and further condensation under reduced pressure to reduce VOC content to less than 10 mg/kg.
The method results in a binder resin with excellent abrasion resistance and significantly reduced VOC content, meeting stringent environmental standards and enhancing the performance of toners in electrophotographic systems.
Smart Images

Figure 0007659951000001 
Figure 0007659951000002 
Figure 0007659951000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a binder resin for a toner, a binder resin for a toner, a toner for developing an electrostatic image, and the like. [Background technology]
[0002] In the field of electrophotography, with the development of electrophotographic systems, there is a demand for the development of toners for developing electrostatic images that can meet the demands of higher image quality and higher speeds.
[0003] With the increasing functionality of toners and toner binders, it is known to use silicone resins as binder resins. Patent Document 1 describes a white toner that includes toner particles having a binder resin and a white pigment, the binder resin including resin A, which includes (i) at least one selected from the group consisting of a siloxane bond and a fluoro group, and an ester bond, and (ii) is contained in an amount of 50% by mass or more in the binder resin, and describes that the white toner can obtain images with high whiteness while maintaining high abrasion resistance. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2020-190648 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, awareness of improving the office environment has increased, and environmental standards have been established mainly in Europe to address the effects on the human body of volatile organic compounds (VOCs), which are the cause of odors emitted from electrophotographic systems, and it has become necessary for electrophotographic systems to also consider the environment and safety and comply with environmental standards. The strictest environmental standard is the "Blue Angel" mark standard, a German eco-labeling system, which requires that the VOC emission rate obtained using the measurement method specified in ECMA-328 / RAL-UZ-122, "Measurement of Chemical Emission Rates from Electronic Equipment," must be below the regulated value. When modified silicone is used in the production of binder resin, in addition to the volatile organic compounds (VOCs) originally contained in the modified silicone, there is a tendency for the amount of volatile organic compounds (VOCs) resulting from the thermal decomposition of the modified silicone during synthesis to increase, resulting in a high content of VOCs in the silicone modified resin produced, which raises concerns that VOCs may be emitted from electrophotographic systems. The present invention relates to a method for producing a binder resin for toner having excellent abrasion resistance and a low VOC content, a binder resin for toner, and a toner for developing electrostatic images. [Means for solving the problem]
[0006] One embodiment of the present invention relates to the following items (1) to (3). [1] A method for producing a binder resin for toner, which is a reaction product of an alcohol component containing a dihydric or higher alcohol, a carboxylic acid component containing a dihydric or higher carboxylic acid compound, and a modified silicone, and has a volatile organic compound content of 10 mg / kg or less, Step 1: A step of condensing the alcohol component, the carboxylic acid component, and the modified silicone to obtain a reaction mixture; Step 2: steam distilling the reaction mixture; and Step 3: applying a reduced pressure to remove water and further condensing the reaction mixture; A method for producing a binder resin for toner comprising the steps of: [2] A toner binder resin which is a reaction product of an alcohol component containing a divalent or higher alcohol, a carboxylic acid component containing a divalent or higher carboxylic acid compound, and a modified silicone, and which has a volatile organic compound content of 10 mg / kg or less. [3] A toner for developing electrostatic images, comprising the binder resin for toners according to [2]. Effect of the Invention
[0007] According to the present invention, it is possible to provide a method for producing a binder resin for toner having excellent abrasion resistance and a low VOC content. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] [Method of manufacturing binder resin for toner] The method for producing a binder resin for toner according to one embodiment of the present invention is a method for producing a binder resin for toner, which is a reaction product of an alcohol component containing a divalent or higher alcohol, a carboxylic acid component containing a divalent or higher carboxylic acid compound, and modified silicone, and has a volatile organic compound content of 10 mg / kg or less. Note that the volatile organic compound content is the content calculated as toluene. The manufacturing method includes: Step 1: A step of condensing the alcohol component, the carboxylic acid component, and the modified silicone to obtain a reaction mixture; Step 2: steam distilling the reaction mixture; and Step 3: applying a reduced pressure to remove water and further condensing the reaction mixture. According to the present invention, it is possible to provide a method for producing a binder resin for a toner that has excellent abrasion resistance and is used for a toner having a low VOC content.
[0009] The reason why the VOC in the toner binder resin is reduced in the manufacturing method of the present invention is not clear, but is thought to be as follows. By introducing step 2, in which the reaction mixture is obtained in step 1 and then steam distilled, water is azeotroped with impurities and pyrolysates in the modified silicone, and volatile organic compounds can be efficiently removed. In addition, by introducing step 3, in which the reaction mixture is further condensed under reduced pressure after steam distillation, volatile organic compounds such as water and pyrolysates can be efficiently removed while suppressing pyrolysis of the modified silicone. At the same time, the mobility of the silicone modified resin in the toner binder resin is activated, and the modified silicone portion is localized on the surface of the toner layer, thereby improving the slipperiness of the printed matter and improving the abrasion resistance of the image.
[0010] The definitions of various terms used in this specification are given below. In the specification, the carboxylic acid compound includes not only the carboxylic acid itself, but also anhydrides that decompose during the reaction to produce an acid, and alkyl esters of each carboxylic acid (alkyl groups having 1 to 3 carbon atoms). Bisphenol A is 2,2-bis(4-hydroxyphenyl)propane. In the present specification, the term "binder resin composition" simply means a resin component contained in a toner, including a binder resin for a toner, an amorphous polyester resin, and a crystalline polyester resin. It is determined by the crystallinity index. The crystallinity index is defined as the ratio of the softening point of the resin to the maximum endothermic peak temperature (softening point (°C) / maximum endothermic peak temperature (°C)) in the measurement method described in the Examples below. Amorphous resins are resins with a crystallinity index of 1.4 or more or less than 0.6, preferably 1.5 or more or 0.5 or less, more preferably 1.6 or more or 0.5 or less. Crystalline resins are resins with a crystallinity index of 0.6 or more and less than 1.4, preferably 0.7 or more, more preferably 0.9 or more, and preferably 1.2 or less. The crystallinity index can be appropriately adjusted depending on the type and ratio of raw material monomers, as well as production conditions such as reaction temperature, reaction time, and cooling rate. The maximum endothermic peak temperature refers to the temperature of the peak on the highest temperature side among the endothermic peaks observed. The crystallinity index can be calculated from the values obtained by the measurement method of the softening point and maximum endothermic peak temperature of the resin described in the Examples.
[0011] [Process 1] Step 1 is a step in which an alcohol component, a carboxylic acid component, and a modified silicone are reacted to obtain a reaction mixture.
[0012] In step 1, if necessary, a reaction mixture may be obtained by condensation using an esterification catalyst such as tin(II) di(2-ethylhexanoate), dibutyltin oxide, titanium diisopropoxybis(triethanolaminate) in an amount of 0.01 part by mass or more and 5 parts by mass or less per 100 parts by mass of the combined amount of the alcohol component and the carboxylic acid component, and an esterification promoter such as gallic acid (same as 3,4,5-trihydroxybenzoic acid) in an amount of 0.001 part by mass or more and 0.5 part by mass or less per 100 parts by mass of the combined amount of the alcohol component and the carboxylic acid component. The reaction may be carried out in an inert gas atmosphere.
[0013] Step 1 is preferably carried out at 200°C or higher, more preferably 210°C or higher, even more preferably 220°C or higher, and preferably at 235°C or lower, more preferably 230°C or lower, even more preferably 225°C or lower. The reaction time in step 1 is not particularly limited as long as it is a time that allows the reaction mixture to reach a desired degree of polymerization, but is preferably 2 hours or more, more preferably 3 hours or more, and is preferably 12 hours or less, more preferably 9 hours or less.
[0014] (Alcohol content) The alcohol component includes dihydric or higher alcohols. Examples of the dihydric or higher alcohol include a diol having an aromatic group (hereinafter also referred to as an "aromatic diol"), a linear or branched aliphatic diol, an alicyclic diol, and a trihydric or higher polyhydric alcohol. Among these, an aromatic diol or a linear or branched aliphatic diol is preferred, and an aromatic diol is more preferred.
[0015] The aromatic diol is preferably an alkylene oxide adduct of bisphenol A, more preferably represented by formula (I):
[0016] [ka] (In the formula, OR 1 and R 2 O is an oxyalkylene group, and R 1 and R 2 are each independently an ethylene group or a propylene group, x and y are each an average number of moles of alkylene oxide added and are each a positive number, and the sum of x and y is 1 or more, preferably 1.5 or more, and 16 or less, preferably 8 or less, and more preferably 4 or less. Examples of the alkylene oxide adduct of bisphenol A include a propylene oxide adduct of bisphenol A and an ethylene oxide adduct of bisphenol A. One or more of these may be used. Among these, it is preferable to use the propylene oxide adduct of bisphenol A alone, or the propylene oxide adduct of bisphenol A and the ethylene oxide adduct of bisphenol A in combination. When the propylene oxide adduct of bisphenol A and the ethylene oxide adduct of bisphenol A are used in combination, the molar ratio of the propylene oxide adduct of bisphenol A to the ethylene oxide adduct of bisphenol A (propylene oxide adduct of bisphenol A / ethylene oxide adduct of bisphenol A) is preferably 20 / 80 or more, more preferably 30 / 70 or more, even more preferably 40 / 60 or more, and is preferably 80 / 20 or less, more preferably 70 / 30 or less, even more preferably 60 / 40 or less. The amount of the alkylene oxide adduct of bisphenol A in the alcohol component is preferably 70 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, and is 100 mol % or less, even more preferably 100 mol %.
[0017] As the linear or branched aliphatic diol, an aliphatic diol having a hydroxyl group bonded to a secondary carbon atom may be used. The aliphatic diol having a hydroxyl group bonded to a secondary carbon atom preferably has 3 or more and 4 or less carbon atoms. Examples of aliphatic diols having a hydroxyl group bonded to a secondary carbon atom include 1,2-propanediol, 1,2-butanediol, 1,3-butanediol, and 2,3-butanediol. When an aliphatic diol having a hydroxyl group bonded to a secondary carbon atom is used as the alcohol component, the amount thereof in the alcohol component is preferably 70 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, and is 100 mol % or less, even more preferably 100 mol %.
[0018] Other linear or branched aliphatic diols include, for example, ethylene glycol, 1,3-propanediol, 1,2-butanediol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol.
[0019] Examples of alicyclic diols include hydrogenated bisphenol A [2,2-bis(4-hydroxycyclohexyl)propane] and adducts of hydrogenated bisphenol A with alkylene oxides having 2 to 4 carbon atoms (average number of moles added: 2 to 12). Examples of trihydric or higher polyhydric alcohols include glycerin, pentaerythritol, trimethylolpropane, and sorbitol. These alcohol components may be used alone or in combination of two or more.
[0020] (Carboxylic acid component) The carboxylic acid component includes a divalent or higher carboxylic acid compound. Examples of the divalent or higher carboxylic acid compound include aromatic dicarboxylic acid compounds, linear or branched aliphatic dicarboxylic acid compounds, alicyclic dicarboxylic acid compounds, and trivalent or higher polyvalent carboxylic acid compounds. Among these, aromatic dicarboxylic acid compounds are preferred.
[0021] Examples of aromatic dicarboxylic acid compounds include phthalic acid, isophthalic acid, and terephthalic acid. Among these, isophthalic acid and terephthalic acid are preferred, and terephthalic acid is more preferred. The amount of the aromatic dicarboxylic acid compound in the carboxylic acid component is preferably 30 mol % or more, more preferably 50 mol % or more, even more preferably 80 mol % or more, even more preferably 90 mol % or more, and 100 mol % or less.
[0022] The carbon number of the linear or branched aliphatic dicarboxylic acid compound is preferably 2 or more, more preferably 4 or more, even more preferably 8 or more, even more preferably 10 or more, and is preferably 22 or less, more preferably 16 or less. Examples of the linear or branched aliphatic dicarboxylic acid compound include oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, sebacic acid, dodecanedioic acid, tetradecanedioic acid, succinic acid substituted with an aliphatic hydrocarbon group having from 1 to 20 carbon atoms, or anhydrides or alkyl esters having from 1 to 3 carbon atoms. Examples of succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms include dodecylsuccinic acid, dodecenylsuccinic acid, and octenylsuccinic acid. Among these, succinic acid substituted with an aliphatic hydrocarbon group having from 1 to 20 carbon atoms, or an anhydride thereof, is preferred. When a linear or branched aliphatic dicarboxylic acid compound is contained, the amount of the linear or branched aliphatic dicarboxylic acid compound in the carboxylic acid component is preferably 2 mol % or more, more preferably 3 mol % or more, even more preferably 5 mol % or more, and preferably 30 mol % or less, more preferably 20 mol % or less, even more preferably 10 mol % or less.
[0023] The trivalent or higher polyvalent carboxylic acid compound is preferably a trivalent carboxylic acid, such as trimellitic acid or its anhydride, of which trimellitic acid or its anhydride is preferred. When a trivalent or higher polyvalent carboxylic acid compound is contained, the amount of the trivalent or higher polyvalent carboxylic acid compound in the carboxylic acid component is preferably 1 mol % or more, more preferably 5 mol % or more, even more preferably 10 mol % or more, even more preferably 15 mol % or more, and is preferably 35 mol % or less, more preferably 30 mol % or less. These carboxylic acid components may be used alone or in combination of two or more.
[0024] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component (COOH groups / OH groups) is preferably 0.6 or more, more preferably 0.7 or more, and is preferably 1.3 or less, more preferably 1.2 or less.
[0025] (Modified silicone) The modified silicone used in the binder resin for the toner is a modified silicone having at least one group selected from an amino group, a carboxy group, an epoxy group, and a carbinol group in a side chain or at an end, preferably in a side chain, from the viewpoint of obtaining a toner for developing electrostatic images having excellent abrasion resistance.
[0026] More specifically, the modified silicone is preferably represented by the formula (1):
[0027] [ka] [wherein, each R is independently a hydrocarbon group having 1 to 6 carbon atoms, each R' is independently an alkylene group having 1 to 10 carbon atoms, a is 1 or 0, each X is independently a group containing an amino group, a carboxy group, an epoxy group, or a hydroxy group, and * is a bonding site], and
[0028] [ka] In the formula, each R is independently a hydrocarbon group having 1 to 6 carbon atoms, and * is a bonding site.
[0029] The terminal of the modified silicone is represented by the formula (3):
[0030] [ka] In the formula, R″ is a hydrocarbon group having 1 to 10 carbon atoms, and * is a bonding site.
[0031] The hydrocarbon group of R has 6 or less carbon atoms, preferably 4 or less, more preferably 3 or less, even more preferably 2 or less, and even more preferably 1 carbon atom. Examples of the hydrocarbon group for R include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a tert-butyl group, a pentyl group, a hexyl group, and a phenyl group. Among these, a methyl group is preferable. The alkylene group of R′ has 10 or less, preferably 8 or less, more preferably 5 or less, even more preferably 4 or less, even more preferably 3 or less, even more preferably 2 or less, and even more preferably 1 carbon atom. Examples of the alkylene group of R' include methanediyl, ethane-1,2-diyl, ethane-1,1-diyl, n-propane-1,3-diyl, n-propane-1,2-diyl, n-butane-1,4-diyl, tert-butane-1,2-diyl, and n-pentane-1,5-diyl. Among these, methanediyl is preferred. The hydrocarbon group of R'' has 10 or less, preferably 8 or less, more preferably 6 or less, even more preferably 4 or less, even more preferably 3 or less, even more preferably 2 or less, and even more preferably 1 carbon atom. Examples of the hydrocarbon group for R'' include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a tert-butyl group, a pentyl group, and a benzyl group.
[0032] Each X is independently a group containing an amino group, a carboxy group, an epoxy group, or a hydroxy group. The amino group, the carboxy group, the epoxy group, and the hydroxy group are collectively referred to as "reactive groups", and the group containing a reactive group and other moieties is also referred to as "reactive group-containing group". Thus, X is a reactive group or a reactive group-containing group. In formula (1), when a is 1, X is a reactive group, and when a is 0, X is a reactive group-containing group.
[0033] When a is 0, X may have an ether bond, or may be a group in which one or more reactive groups are substituted on a hydrocarbon group in which some methylene groups are substituted with ether bonds. That is, X may be an aliphatic hydrocarbon group which may have an ether bond and is substituted with one or more amino groups, carboxy groups, epoxy groups, or hydroxy groups, and the total number of carbon atoms in X is preferably 10 or less, more preferably 9 or less, and preferably 1 or more, more preferably 2 or more.
[0034] The weight average molecular weight (Mw) of the modified silicone is preferably 600 or more, more preferably 2,000 or more, even more preferably 5,000 or more, even more preferably 10,000 or more, and preferably 200,000 or less, more preferably 100,000 or less, even more preferably 70,000 or less, even more preferably 60,000 or less, even more preferably 50,000 or less, even more preferably 40,000 or less. The number average molecular weight (Mn) of the modified silicone is preferably 500 or more, more preferably 700 or more, and even more preferably 800 or more, and is preferably 10,000 or less, more preferably 5,000 or less, more preferably 4,000 or less, more preferably 3,000 or less, and even more preferably 2,000 or less.
[0035] From the viewpoint of obtaining a toner for developing electrostatic images having excellent abrasion resistance, the modified silicone is preferably (i) a modified silicone having an amino group on a side chain or at an end, or (ii) Modified silicone having at least one group selected from a carboxy group, an epoxy group, and a carbinol group in the side chain, more preferably a modified silicone having an amino group in the side chain.
[0036] As the modified silicone, from the viewpoint of obtaining a toner having excellent abrasion resistance, a modified silicone (a) having an amino group on the side chain (hereinafter, also simply referred to as "modified silicone (a)") is preferable. The modified silicone (a) is represented by the following formula (1a 0 ):
[0037] [ka] A repeating unit represented by the formula: (wherein R is independently a hydrocarbon group having from 1 to 5 carbon atoms, R' is independently an alkylene group having from 1 to 10 carbon atoms, a is 1 or 0, X is independently -NH2 or -R'''-NH-R'''-NH2, R''' is independently an alkylene group having from 1 to 5 carbon atoms, and * is a bonding site), Preferably, the compound of formula (1a):
[0038] [ka] (wherein R, R', a, and * are defined as in the above formula (1)), and a repeating unit represented by formula (2):
[0039] [ka] (wherein R and * are defined as in the above formula (2)) Formula (1a 0 In formula (1a), when a is 1, X is -NH2, and when a is 0, X is -R'''-NH-R'''-NH2. In formula (1a), a is 1, and R' is an alkylene group having 1 to 10 carbon atoms. In formula (1a), *-(R') a Examples of the group represented by -NH2 include the following substituents 1a-1 to 1a-3.
[0040] [ka]
[0041] The terminal of the modified silicone (a) is represented by the formula (3):
[0042] [ka] [wherein R″ and * are defined as in the above formula (3)].
[0043] The kinetic viscosity of the modified silicone (a) at 25° C. is preferably 500 mm 2 / s or more, preferably 1,000 mm 2 / s or more, and more preferably 1,500 mm 2 / s or more, and preferably 3,000 mm 2 / s or less, preferably 2,000 mm 2 / s or less, and more preferably 1,800 mm 2 / s or less. The kinetic viscosity of the modified silicone (a) is measured at 25° C. using a fully automatic micro dynamic viscometer (manufactured by Viscotec Co., Ltd.).
[0044] The functional group equivalent of the modified silicone (a) is preferably 300 g / mol or more, more preferably 1,000 g / mol or more, even more preferably 2,000 g / mol or more, even more preferably 3,000 g / mol or more, and is preferably 6,000 g / mol or less, more preferably 5,000 g / mol or less, even more preferably 4,500 g / mol or less. The functional group equivalent means the mass of the modified silicone per mole of functional group.
[0045] An example of the modified silicone (a) is a modified silicone having an amino group on the side chain (a commercially available product is, for example, "KF-864" (manufactured by Shin-Etsu Chemical Co., Ltd.)).
[0046] The amount of the modified silicone (a) used in the binder resin for toner is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 2 parts by mass or more, relative to 100 parts by mass of the theoretical yield of the polyester obtained from the alcohol component and the carboxylic acid component in the raw materials, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 6 parts by mass or less.
[0047] As the modified silicone, from the viewpoint of obtaining a toner having excellent abrasion resistance, a modified silicone (b) having at least one group selected from a carboxy group, an epoxy group, and a carbinol group in a side chain (hereinafter, also simply referred to as "modified silicone (b)") is preferable. More specifically, the modified silicone (b) is preferably represented by the formula (1b):
[0048] [ka] (wherein R, R', a, and * are defined as in the above formula (1), each X' is independently a group containing a carboxy group, an epoxy group, or a hydroxy group, and * is a bonding site.)
[0049] [ka] (wherein R and * are defined as in the above formula (2))
[0050] When the modified silicone (b) is a modified silicone having a carboxy group in the side chain, X' is a group containing a carboxy group. It is preferable that a is 1, X' is a carboxy group (-COOH), and R' is preferably an alkylene group having 1 to 10 carbon atoms, more preferably an alkylene group having 1 to 5 carbon atoms, and even more preferably an alkylene group having 1 to 3 carbon atoms. Furthermore, when the modified silicone (b) is a modified silicone having a carboxy group on the side chain and a is 0, X' may be an aliphatic hydrocarbon group substituted with a carboxy group and preferably containing an ether bond having from 1 to 10 carbon atoms, more preferably an aliphatic hydrocarbon group containing an ether bond having from 1 to 6 carbon atoms. Note that an aliphatic hydrocarbon group containing an ether bond refers to one having an ether bond (-O-) between carbon-carbon bonds.
[0051] When the modified silicone (b) is a modified silicone having an epoxy group in the side chain, X' is a group containing an epoxy group. a is 1 and X' is an epoxy group, or a is 0 and X' is an aliphatic hydrocarbon group containing an epoxy group and preferably having 1 to 10 carbon atoms and optionally containing an ether bond, more preferably having 1 to 6 carbon atoms and optionally containing an ether bond.
[0052] When the modified silicone (b) is a modified silicone having a hydrocarbyl group on the side chain, X' is a group containing a hydroxy group. a is 1 and X' is a hydroxy group, or a is 0 and X' is an aliphatic hydrocarbon group substituted with a hydroxy group and preferably having 1 to 10 carbon atoms and optionally containing an ether bond, more preferably having 1 to 6 carbon atoms and optionally containing an ether bond, and the number of hydroxy groups in X' is 1 or more, preferably 5 or less, more preferably 4 or less, and even more preferably 2 or less.
[0053] In formula (1b), *-(R') a Examples of the group represented by -X' include the following substituents 1b-1 to 1b-9.
[0054] [ka]
[0055] The terminal of the modified silicone (b) is represented by the formula (3):
[0056] [ka] [wherein R″ and * are defined as in the above formula (3)].
[0057] The kinetic viscosity of the modified silicone (b) at 25° C. is preferably 10 mm 2 / s or more, preferably 15 mm 2 / s or more, more preferably 20 mm 2 / s or more, and preferably 3,000 mm 2 / s or less, preferably 2,800 mm 2 / s or less, and more preferably 2,600 mm 2 / s or less. The kinetic viscosity of the modified silicone (b) is measured at 25° C. using a fully automatic micro dynamic viscometer (manufactured by Viscotec Co., Ltd.).
[0058] The functional group equivalent of the modified silicone (b) is preferably 300 g / mol or more, more preferably 500 g / mol or more, and preferably 6,000 g / mol or less, more preferably 5,000 g / mol or less, and even more preferably 4,000 g / mol or less. The functional group equivalent means the mass of the modified silicone per mole of functional group.
[0059] Examples of the modified silicone (b) include modified silicones having a carboxy group on the side chain (commercially available products include "X-22-3701E" (manufactured by Shin-Etsu Chemical Co., Ltd.) and "BY16-880" (manufactured by Dow Corning Toray Co., Ltd.)), modified silicones having an epoxy group on the side chain (commercially available product includes "X-22-343" (manufactured by Shin-Etsu Chemical Co., Ltd.)), and modified silicones having a hydroxy group on the side chain (commercially available product includes "X-22-4039" (manufactured by Shin-Etsu Chemical Co., Ltd.)).
[0060] The amount of the modified silicone (b) used in the toner binder resin is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 2 parts by mass or more, relative to 100 parts by mass of the theoretical yield of the polyester obtained from the alcohol component and the carboxylic acid component in the raw materials, and is preferably 10 parts by mass or less, and more preferably 7 parts by mass or less.
[0061] [Process 2] Step 2 is a process in which the reaction mixture obtained in step 1 is subjected to steam distillation, and VOCs are separated and removed from the reaction mixture.
[0062] The VOCs contained in the reaction mixture include cyclic siloxanes, such as hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentanesiloxane, dodecamethylcyclohexanesiloxane, etc. The reaction mixture may also contain VOCs such as 2-phenoxyethanol, 1-phenoxy-2-propanol, etc.
[0063] Steam distillation may be carried out by introducing steam into the reaction system, or by generating steam in the reaction system by dripping water into the reaction system. From the viewpoint of ease of operation, it is preferable to generate steam in the reaction system by dripping water into the reaction system. In order to efficiently separate VOCs from the reaction mixture, the supply amount of steam or water is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 6 parts by mass or more, based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component in the raw material. In addition, from the viewpoint of simplifying the removal of moisture after the end of step 2, the supply amount of steam or water is preferably 10 parts by mass or less, more preferably 9.5 parts by mass or less, and even more preferably 9 parts by mass or less, based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component in the raw material.
[0064] The steam distillation is preferably carried out at 180° C. or higher in order to retain steam in the reaction mixture and efficiently separate VOCs, and is also carried out at a temperature lower than the temperature at which the condensation in step 1 is carried out, more preferably at 200° C. or lower, in order to suppress further generation of VOCs due to decomposition of the reaction mixture. The difference between the temperature at which the steam distillation is carried out and the temperature at which the condensation in step 1 is carried out is preferably 20° C. or higher, more preferably 25° C. or higher, and is preferably 60° C. or lower, more preferably 50° C. or lower.
[0065] In the case of steam distillation, when water is added dropwise to the reaction system to generate steam within the reaction system, the addition of water is preferably carried out over 30 minutes or more, more preferably over 1 hour or more. On the other hand, when steam is introduced into the reaction system, the introduction of steam may be carried out in a short period of time, but is preferably carried out over 30 minutes or more, more preferably over 1 hour or more.
[0066] The steam distillation is usually carried out at normal pressure, but may be carried out at a slightly reduced pressure.
[0067] [Step 3] In step 3, the reaction system is depressurized to remove water and VOCs, and the reaction mixture is further condensed. After the steam distillation in step 2, the reaction system is depressurized to remove water and VOCs, and the condensation of the reaction mixture further proceeds as water is sufficiently removed from the reaction system.
[0068] In order to remove moisture and VOCs and condense the reaction mixture, step 3 is preferably carried out at 180° C. or higher, and in order to suppress further generation of VOCs due to decomposition of the reaction mixture, step 3 is preferably carried out at the same temperature as that at which steam distillation in step 2 is carried out or at a lower temperature than that at which steam distillation in step 2 is carried out, more preferably at 200° C. or lower. When the temperature at which condensation in step 3 is carried out is lower than that at which steam distillation is carried out, the difference therebetween is preferably 1° C. or higher, more preferably 3° C. or higher, and preferably 20° C. or lower, more preferably 10° C. or lower. In addition, the pressure in step 3 should be reduced to such an extent that the water remaining from the steam distillation in step 2 and the water and VOCs produced by condensation are removed, and the pressure is preferably 3 kPa or more, more preferably 5 kPa or more, and is preferably 70 kPa or less, more preferably 40 kPa or less, even more preferably 20 kPa or less, and even more preferably 10 kPa or less.
[0069] [Binding resin for toner] The binder resin for toner according to one embodiment of the present invention is a reaction product of an alcohol component containing a divalent or higher alcohol, a carboxylic acid component containing a divalent or higher carboxylic acid compound, and modified silicone, and has a volatile organic compound (VOC) content of 10 mg / kg or less. The VOC content is calculated as a toluene content. Hereinafter, the binder resin for toner according to one embodiment of the present invention is also referred to as a "low-VOC toner binder resin." The low-VOC toner binder resin can be produced by the above-mentioned production method. The binder resin for low-VOC toner may contain, in addition to the reactants, trace amounts of unreacted alcohol components, carboxylic acid components, and modified silicones, as well as compounds derived from the catalyst and co-catalyst added in step 1 of the above-mentioned production method.
[0070] The binder resin for low VOC toner is preferably an amorphous polyester.
[0071] [Physical properties of binder resin for low VOC toner] The VOC content of the binder resin for low-VOC toner is 10 mg / kg or less, preferably 7.5 mg / kg or less, more preferably 5.0 mg / kg or less, even more preferably 4.0 mg / kg or less, and even more preferably 3.0 mg / kg or less. The lower limit of the VOC content is not particularly limited. The VOC content is measured by the method described in the examples and is expressed in terms of toluene.
[0072] The acid value of the binder resin for low-VOC toner is preferably 0.1 mgKOH / g or more, more preferably 0.5 mgKOH / g or more, even more preferably 1 mgKOH / g or more, even more preferably 3 mgKOH / g or more, and is preferably 40 mgKOH / g or less, more preferably 30 mgKOH / g or less, even more preferably 20 mgKOH / g or less, even more preferably 10 mgKOH / g or less.
[0073] The hydroxyl value of the binder resin for low-VOC toner is preferably 0.1 mgKOH / g or more, more preferably 10 mgKOH / g or more, even more preferably 20 mgKOH / g or more, and is preferably 100 mgKOH / g or less, more preferably 90 mgKOH / g or less, even more preferably 80 mgKOH / g or less.
[0074] The softening point of the binder resin for low-VOC toner is preferably 70° C. or higher, more preferably 75° C. or higher, and even more preferably 80° C. or higher, from the viewpoint of further improving abrasion resistance, and is preferably 140° C. or lower, more preferably 130° C. or lower, more preferably 125° C. or lower, even more preferably 120° C. or lower, and even more preferably 110° C. or lower, from the viewpoint of further improving low-temperature fixing ability.
[0075] The glass transition temperature of the binder resin for low-VOC toner is preferably 30° C. or higher, more preferably 40° C. or higher, and even more preferably 45° C. or higher, from the viewpoint of further improving storage stability, and is preferably 80° C. or lower, more preferably 70° C. or lower, and even more preferably 60° C. or lower, from the viewpoint of further improving low-temperature fixing ability.
[0076] The number average molecular weight of the binder resin for low-VOC toner is preferably 1,000 or more, more preferably 1,500 or more, from the viewpoint of excellent abrasion resistance, and is preferably 8,000 or less, more preferably 6,000 or less, and even more preferably 4,000 or less, from the viewpoint of excellent low-temperature fixing property.
[0077] The weight average molecular weight of the binder resin for low-VOC toner is preferably 1,000 or more, more preferably 1,500 or more, even more preferably 2,000 or more, and even more preferably 3,000 or more, from the viewpoint of excellent abrasion resistance, and is preferably 10,000 or less, more preferably 8,000 or less, and even more preferably 6,000 or less, from the viewpoint of excellent low-temperature fixing property.
[0078] The acid value, softening point, glass transition temperature, number average molecular weight, and weight average molecular weight of the binder resin for low-VOC toner can be appropriately adjusted by the type and amount of raw material monomer used, as well as production conditions such as reaction temperature, reaction time, and cooling rate, and these values can be determined by the methods described in the examples. When two or more kinds of reaction products are used in combination, it is preferable that the acid value, hydroxyl value, softening point and glass transition temperature obtained as a mixture thereof are each within the above-mentioned ranges.
[0079] From the viewpoint of further improving the abrasion resistance of the toner for developing electrostatic images, the content of the binder resin for low-VOC toner in the binder resin composition of the toner for developing electrostatic images is preferably 35% by mass or more, more preferably 40% by mass or more, even more preferably 45% by mass or more, even more preferably 50% by mass or more, and is preferably 90% by mass or less, more preferably 85% by mass or less, even more preferably 80% by mass or less, and even more preferably 70% by mass or less.
[0080] [Toner for developing electrostatic images] The toner for developing electrostatic images according to one embodiment of the present invention contains the above-mentioned binder resin for low VOC toners, from the viewpoint of obtaining a toner having excellent abrasion resistance. The toner for developing electrostatic images contains, for example, toner particles and external additives.
[0081] <Toner particles> The toner particles include the above-mentioned low VOC toner binder resin. From the viewpoint of further improving the abrasion resistance, the toner particles preferably further contain an amorphous polyester resin other than the above-mentioned binder resin for low VOC toner. The toner particles may further contain additives such as a release agent (wax), a charge control agent, a colorant, a magnetic powder, a flowability improver, a conductivity adjuster, a reinforcing filler such as a fibrous substance, an antioxidant, an antiaging agent, and a cleaning property improver.
[0082] [Amorphous polyester resin] The amorphous polyester resin is a polycondensation product of an alcohol component and a carboxylic acid component, and the alcohol component and the carboxylic acid component are as exemplified in the method for producing a binder resin for toner.
[0083] (Physical properties of amorphous polyester resin) The acid value of the amorphous polyester resin is preferably 0.1 mgKOH / g or more, more preferably 2 mgKOH / g or more, even more preferably 5 mgKOH / g or more, even more preferably 10 mgKOH / g or more, and is preferably 40 mgKOH / g or less, more preferably 30 mgKOH / g or less, even more preferably 20 mgKOH / g or less.
[0084] The hydroxyl value of the amorphous polyester resin is preferably 0.1 mgKOH / g or more, more preferably 20 mgKOH / g or more, even more preferably 30 mgKOH / g or more, and is preferably 60 mgKOH / g or less, more preferably 50 mgKOH / g or less, even more preferably 45 mgKOH / g or less.
[0085] The difference between the softening point of the amorphous polyester resin and the softening point of the binder resin for low-VOC toner is preferably 5°C or more, more preferably 10°C or more, even more preferably 15°C or more, and is preferably 60°C or less, more preferably 50°C or less, even more preferably 40°C or less. The softening point of the amorphous polyester resin is preferably higher than the softening point of the binder resin for low VOC toner. From the viewpoint of further improving abrasion resistance, the softening point of the amorphous polyester resin is preferably 80°C or higher, more preferably 90°C or higher, even more preferably 100°C or higher, and even more preferably 110°C or higher, and is preferably 160°C or lower, more preferably 150°C or lower, even more preferably 140°C or lower, and even more preferably 130°C or lower.
[0086] The glass transition temperature of the amorphous polyester resin is preferably 50°C or higher, more preferably 55°C or higher, and even more preferably 60°C or higher, and is preferably 80°C or lower, more preferably 75°C or lower, and even more preferably 70°C or lower.
[0087] The acid value, hydroxyl value, softening point and glass transition temperature of the amorphous polyester resin can be appropriately adjusted by the types and amounts of raw material monomers used, as well as production conditions such as reaction temperature, reaction time and cooling rate, and these values can be determined by the methods described in the examples. When two or more kinds of amorphous polyester resins are used in combination, it is preferable that the acid value, hydroxyl value, softening point and glass transition temperature of the mixture are each within the above-mentioned ranges.
[0088] The amorphous polyester resin can be obtained, for example, by polycondensation of an alcohol component and a carboxylic acid component. The polycondensation conditions can be the same as those shown in step 1 of the above-mentioned method for producing a binder resin for toner.
[0089] When an amorphous polyester-based resin is contained, the mass ratio of the binder resin for low-VOC toner to the amorphous polyester-based resin [binder resin for low-VOC toner / amorphous polyester-based resin] is, from the viewpoint of improving abrasion resistance, preferably 10 / 90 or more, more preferably 30 / 70 or more, even more preferably 50 / 50 or more, even more preferably 60 / 40 or more, and is preferably 90 / 10 or less, more preferably 80 / 20 or less, even more preferably 70 / 30 or less.
[0090] When an amorphous polyester resin is contained, the content of the amorphous polyester resin in the binder resin composition of the toner is, from the viewpoint of improving the abrasion resistance, preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, and preferably 65% by mass or less, more preferably 60% by mass or less, even more preferably 55% by mass or less, even more preferably 50% by mass or less.
[0091] [Crystalline polyester resin] The toner particles preferably contain a crystalline polyester resin. The crystalline polyester resin is, for example, a polycondensation product of an alcohol component and a carboxylic acid component. The alcohol component and the carboxylic acid component of the crystalline polyester resin will be described below.
[0092] The alcohol component preferably comprises an α,ω-aliphatic diol. The α,ω-aliphatic diol has preferably 2 or more, more preferably 4 or more, and even more preferably 5 or more, and preferably 14 or less, more preferably 12 or less, and even more preferably 10 or less. Examples of α,ω-aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, and 1,14-tetradecanediol. Among these, ethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,10-decanediol, and 1,12-dodecanediol are preferred, and 1,6-hexanediol is more preferred.
[0093] The amount of α,ω-aliphatic diol in the alcohol component is preferably 80 mol% or more, more preferably 85 mol% or more, even more preferably 90 mol% or more, even more preferably 95 mol% or more, and is 100 mol% or less, even more preferably 100 mol%.
[0094] The alcohol component may contain other alcohol components different from the α,ω-aliphatic diols. Examples of the other alcohol components include aliphatic diols other than the α,ω-aliphatic diols, aromatic diols, alicyclic diols, and trihydric or higher polyhydric alcohols.
[0095] The carboxylic acid component is preferably an aliphatic dicarboxylic acid, and the aliphatic dicarboxylic acid is preferably a straight-chain aliphatic dicarboxylic acid. The aliphatic dicarboxylic acid has preferably 2 or more, more preferably 4 or more, and even more preferably 6 or more carbon atoms, and preferably 14 or less, and more preferably 13 or less carbon atoms. Examples of the aliphatic dicarboxylic acid include oxalic acid, malonic acid, fumaric acid, maleic acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanedioic acid, and tetradecanedioic acid. Among these, dodecanedioic acid and tetradecanedioic acid are preferred.
[0096] The content of the aliphatic dicarboxylic acid in the carboxylic acid component is preferably 85 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, and is preferably 100 mol % or less, more preferably 98 mol % or less.
[0097] The carboxylic acid component may contain, in addition to an aliphatic dicarboxylic acid, an aromatic dicarboxylic acid, an alicyclic dicarboxylic acid, or a polyvalent carboxylic acid having three or more carboxylic acids. Examples of the aromatic dicarboxylic acid, the alicyclic dicarboxylic acid, and the trivalent or higher polyvalent carboxylic acid are the same as those exemplified in the method for producing a binder resin for a toner. From the viewpoint of adjusting the molecular weight and softening point of the crystalline polyester resin, the carboxylic acid component may appropriately contain a monovalent carboxylic acid. These may be used alone or in combination of two or more kinds.
[0098] The monovalent carboxylic acid is preferably a monovalent long-chain aliphatic monocarboxylic acid, and examples of such compounds include aliphatic monocarboxylic acids having 10 to 22 carbon atoms, such as capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, and behenic acid, and alkyl esters of these acids in which the alkyl group has 1 to 3 carbon atoms.
[0099] From the viewpoint of abrasion resistance, the content of the monovalent carboxylic acid in the carboxylic acid component is preferably 1 mol % or more, more preferably 1.5 mol % or more, even more preferably 2 mol % or more, and preferably 5 mol % or less, more preferably 4.5 mol % or less, even more preferably 4 mol % or less.
[0100] The equivalent ratio of the carboxyl group (COOH group) of the carboxylic acid component to the hydroxyl group (OH group) of the alcohol component [COOH group / OH group] is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.
[0101] The crystalline polyester resin can be produced, for example, by polycondensing raw material monomers containing an alcohol and a carboxylic acid compound in an inert gas atmosphere, preferably in the presence of an esterification catalyst, and if necessary, in the presence of an esterification promoter, a polymerization inhibitor, etc., at a temperature of preferably 130°C or higher, more preferably 170°C or higher, and preferably 250°C or lower, more preferably 240°C or lower.
[0102] The softening point of the crystalline polyester resin is preferably 60° C. or higher, more preferably 70° C. or higher, and even more preferably 75° C. or higher, from the viewpoint of further improving the storage stability of the toner, and is preferably 150° C. or lower, more preferably 120° C. or lower, and even more preferably 100° C. or lower, from the viewpoint of further improving the abrasion resistance.
[0103] The melting point of the crystalline polyester resin is preferably 50°C or higher, more preferably 60°C or higher, and even more preferably 65°C or higher from the viewpoint of further improving the storage stability of the toner, and is preferably 100°C or lower, and even more preferably 90°C or lower from the viewpoint of further improving the low-temperature fixing property of the toner.
[0104] The acid value of the crystalline polyester resin is preferably 0.5 mgKOH / g or more, more preferably 0.8 mgKOH / g or more, even more preferably 1 mgKOH / g or more, and is preferably 40 mgKOH / g or less, more preferably 20 mgKOH / g or less, even more preferably 10 mgKOH / g or less.
[0105] The hydroxyl value of the crystalline polyester resin is preferably 2 mgKOH / g or more, more preferably 5 mgKOH / g or more, even more preferably 8 mgKOH / g or more, and is preferably 40 mgKOH / g or less, more preferably 20 mgKOH / g or less, even more preferably 15 mgKOH / g or less.
[0106] The number average molecular weight of the crystalline polyester resin is preferably 1,000 or more, more preferably 2,000 or more, and even more preferably 3,000 or more, and is preferably 50,000 or less, more preferably 20,000 or less, and even more preferably 10,000 or less.
[0107] The weight average molecular weight of the crystalline polyester resin is preferably 2,000 or more, more preferably 5,000 or more, and even more preferably 10,000 or more, and is preferably 50,000 or less, and more preferably 30,000 or less.
[0108] [Release agent (wax)] Examples of the release agent (wax) include hydrocarbon wax, ester wax, silicone wax, and fatty acid amide wax. Examples of the hydrocarbon wax include mineral or petroleum-based hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax; and synthetic hydrocarbon waxes such as polyolefin waxes such as polyethylene wax, polypropylene wax, and polybutene wax. Examples of the ester wax include mineral or petroleum-based ester waxes such as montan wax; vegetable-based ester waxes such as carnauba wax, rice wax, and candelilla wax; and animal-based ester waxes such as beeswax. Examples of fatty acid amide waxes include oleic acid amide and stearic acid amide. These may be used alone or in combination. Among these, the hydrocarbon wax or ester wax is preferable, and the hydrocarbon wax is more preferable. As the hydrocarbon wax, paraffin wax is preferable.
[0109] The melting point of the wax is preferably 60° C. or higher, more preferably 70° C. or higher, and preferably 160° C. or lower, more preferably 150° C. or lower, and even more preferably 140° C. or lower. When two or more waxes are used in combination, it is preferable that the melting point of each wax is within the above-mentioned range. When a wax is contained, the content of the wax is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, even more preferably 0.5 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less, relative to 100 parts by mass of the binder resin composition.
[0110] [Charge control agent] The charge control agent may contain either a positively chargeable charge control agent or a negatively chargeable charge control agent. Examples of the positively charged charge control agent include nigrosine dyes such as "Nigrosine Base EX", "Oil Black BS", "Oil Black SO", "Bontron N-01", "Bontron N-04", "Bontron N-07", "Bontron N-09", "Bontron N-11", "Bontron N-71", "Bontron N-74", and "Bontron N-79" (all manufactured by Orient Chemical Industries Co., Ltd.); triphenylmethane dyes having a tertiary amine as a side chain; quaternary ammonium salt compounds such as "Bontron P-51" (manufactured by Orient Chemical Industries Co., Ltd.), cetyltrimethylammonium bromide, and "COPY CHARGE PX Examples of such resins include "VP435" (manufactured by Clariant), polyamine resins such as "AFP-B" (manufactured by Orient Chemical Industry Co., Ltd.), imidazole derivatives such as "PLZ-2001" and "PLZ-8001" (both manufactured by Shikoku Chemical Industry Co., Ltd.), and styrene-acrylic resins such as "FCA-701PT" (manufactured by Fujikura Chemical Industry Co., Ltd.).
[0111] Examples of negatively chargeable charge control agents include metal-containing azo dyes such as "Varifast Black 3804", "Bontron S-31", "Bontron S-32", "Bontron S-34", and "Bontron S-36" (all manufactured by Orient Chemical Industry Co., Ltd.), "Aizen Spiron Black TRH", and "T-77" (manufactured by Hodogaya Chemical Industry Co., Ltd.); metal compounds of benzilic acid compounds such as "LR-147" and "LR-297" (both manufactured by Nippon Carlit Co., Ltd.); metal compounds of salicylic acid compounds such as "Bontron E-81", "Bontron E-84", "Bontron E-88", and "Bontron E-304" (all manufactured by Orient Chemical Industry Co., Ltd.), and "TN-105" (manufactured by Hodogaya Chemical Industry Co., Ltd.); copper phthalocyanine dyes; quaternary ammonium salts such as "COPY CHARGE NX VP434" (manufactured by Clariant), nitroimidazole derivatives, and organometallic compounds. Among the charge control agents, negatively chargeable charge control agents are preferred, and metal compounds of salicylic acid compounds are more preferred.
[0112] The content of the charge control agent is preferably 0.01 parts by mass or more, more preferably 0.2 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less, based on 100 parts by mass of the binder resin composition. From the viewpoint of improving the environmental stability of the charge amount of the toner, a positively chargeable charge control agent and a negatively chargeable charge control agent may be used in combination.
[0113] The toner of the present invention may contain a charge control resin in addition to or instead of the charge control agent. Examples of the charge control resin include styrene acrylic resin, polyamine resin, and phenol resin.
[0114] [Coloring Agent] As the colorant, any of the dyes, pigments, etc. used as colorants for toners can be used, such as carbon black, phthalocyanine blue, permanent brown FG, brilliant fast scarlet, pigment green B, rhodamine B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, disazo yellow, etc. can be used, and the toner of the present invention may be either a black toner or another color toner. For example, for yellow toner, CI Pigment Yellow (PY) 3, 12, 13, 14, 16, 17, 55, 65, 73, 74, 83, 94, 95, 97, 120, 151, 154, 167, 169, 172, 180, 181, 185 and mixed pigments thereof can be mentioned. For magenta toner, CI Pigment Red (PR) 5, 31, 57:1, 122, 146, 147, 150, 176, 184, 185, 202, 269, CI Pigment Violet (PV) 19 and mixed pigments thereof can be mentioned. For cyan toner, CI Pigment Blue (PB) 15:3, mixed pigments of CI Pigment Blue 15:3 and CI Pigment Green (PG) 7 or CI Pigment Green 36 can be mentioned. In this case, the mixed pigment may be a combination of the respective pigments when blending the raw materials for the toner, or the two pigments may be mixed in advance with the same particle size and then blended with other toner raw materials.
[0115] From the viewpoint of improving the image density of the toner, the content of the colorant is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the binder resin composition.
[0116] [Toner manufacturing method] The toner may be obtained by any known method such as a melt-kneading method, an emulsion phase inversion method, a polymerization method, or an emulsion aggregation method. From the viewpoints of productivity and dispersibility of the colorant, however, a pulverized toner obtained by a melt-kneading method is preferred. In the case of a pulverized toner by a melt-kneading method, the method for producing the toner is preferably Step A: melting and kneading a toner raw material containing a binder resin for low-VOC toner; and Step B: A step of pulverizing and classifying the molten mixture obtained in step A to obtain toner particles. Includes. In step A, for example, raw materials such as a binder resin for low-VOC toner, an amorphous polyester resin, a wax, a charge control agent, a colorant, etc. can be uniformly mixed in a mixer such as a Henschel mixer, and then melt-kneaded in an internal kneader, a single-screw or twin-screw extruder, an open roll-type kneader, etc. In step A, the mixture containing the above-mentioned toner raw materials may be melt-kneaded within a range of 80° C. or more and 160° C. or less. The melt-kneading temperature is preferably 80° C. or more, more preferably 90° C. or more, and is preferably 160° C. or less, more preferably 150° C. or less. In the step A, the melt-kneaded product may be cooled after melt-kneading and then subjected to the next step B.
[0117] In the step B, the melt-kneaded product obtained by the melt-kneading is preferably pulverized and classified to obtain toner particles. The pulverization and classification can be performed by a known method. Furthermore, the obtained toner particles can be subjected to a spheronization step in which the toner shape is made spherical by a known method using a mechanical surface modifying device or a thermal surface modifying device.
[0118] The volume median particle size of toner particles (D 50 From the viewpoint of obtaining a high-quality image, the thickness is preferably 2 μm or more, more preferably 4 μm or more, even more preferably 6 μm or more, and is preferably 14 μm or less, more preferably 12 μm or less, even more preferably 10 μm or less.
[0119] The toner is preferably treated by adding a fluidizing agent or the like as an external additive to the surface of the toner particles. Examples of external additives include inorganic material particles such as hydrophobic silica, titanium oxide, alumina, cerium oxide, and carbon black, and polymer particles such as polycarbonate, polymethyl methacrylate, and silicone resin. Among these, silica is preferred, and from the viewpoint of environmental stability, the silica is preferably hydrophobic silica that has been hydrophobized. The method of hydrophobization is not particularly limited, and examples of hydrophobizing agents include hexamethyldisilazane (HMDS), dimethyldichlorosilane (DMDS), silicone oil, and methyltriethoxysilane, with hexamethyldisilazane being preferred among these. The amount of the hydrophobizing agent to be treated is 1 mg / m per surface area of the silica particles. 2 More than 7mg / m 2 The following is preferred: From the viewpoints of chargeability and prevention of scratches on the photoreceptor, the number average particle size of the external additive is preferably 3 nm or more, more preferably 5 nm or more, and is preferably 300 nm or less, more preferably 200 nm or less. When an external additive is used, the amount of the external additive added is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, even more preferably 0.5 parts by mass or more, and is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less, relative to 100 parts by mass of the toner particles.
[0120] Toners are used to develop latent images formed in electrophotography, electrostatic recording, electrostatic printing, etc. Toners can be used as one-component developers, or mixed with a carrier to form two-component developers. EXAMPLES
[0121] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Physical properties of resins and the like were measured by the following methods.
[0122] [Measurement method] [Content of volatile organic compounds (VOCs) in toner binder resin and comparative toner binder resin] (Measurement of standard toluene solution) 100 mg of toluene was weighed into a 100 mL measuring flask and diluted with methanol to prepare a standard toluene solution. 10 μL of the standard toluene solution was placed in a 20 mL headspace vial and quickly sealed with an aluminum cap. The headspace gas was measured under the conditions shown below.
[0123] (Sample Measurement) 30 to 40 g of the binder resin for toner or the binder resin for comparative toner was ground for 15 seconds in a coffee mill, and 500 mg of the resulting finely ground material was weighed out and placed in a 20 mL headspace vial, which was then sealed with an aluminum cap. The vial containing the sample was placed in a headspace sampler "Agilent 7697" (Agilent Technologies) and heated at 120°C for 60 minutes. The headspace gas was then introduced into a gas chromatograph "Agilent 7890B" (Agilent Technologies) and measurements were performed under the conditions shown below. The amount of VOC in the resin was calculated in toluene equivalent from the peak area obtained by the measurement and the toluene peak area measured above.
[0124] (Measurement conditions) Headspace sampler conditions Oven temperature: 120℃ Loop temperature: 170℃ Line temperature: 200℃ Vial equilibration time: 60 min ·GC measurement conditions Column: HP-5MS (φ0.25 mm × 60 m (film thickness 0.25 μm): Agilent Technologies) Detector: FID Oven temperature rise conditions: Initial temperature 40°C (held for 3 minutes) First stage heating rate: 2℃ / min (up to 70℃) Second stage heating rate: 5℃ / min (up to 150℃) 3rd stage heating rate: 10℃ / min (up to 300℃) Final temperature: 300℃ (held for 5 minutes) Inlet temperature: 200℃ Detector temperature: 300℃ Split ratio: 10:1 Column flow rate: 1mL / min (He)
[0125] [Acid value and hydroxyl value of resin] The acid value and hydroxyl value of the resin were measured based on the neutralization titration method of JIS K0070: 1992. However, only the measurement solvent was changed from the mixed solvent of ethanol and ether specified in JIS K0070: 1992 to a mixed solvent of acetone and toluene [acetone:toluene=1:1 (volume ratio)] for the toner binder resin, comparative toner binder resin, and amorphous polyester resin, and to chloroform for the crystalline polyester resin.
[0126] [Number average molecular weight and weight average molecular weight of resin] The molecular weight distribution was measured by gel permeation chromatography (GPC) according to the following method, and the number average molecular weight and weight average molecular weight were determined. (1) Preparation of sample solution The sample was dissolved in a solvent at 25° C. to a concentration of 0.5 g / 100 mL. Next, this solution was filtered using a fluororesin filter "DISMIC-25JP" (manufactured by ADVANTEC) with a pore size of 0.2 μm to remove insoluble matter, and a sample solution was obtained. Note that when the sample was a toner binder resin, a comparative toner binder resin, or an amorphous polyester resin, tetrahydrofuran was used as the solvent, and when the sample was a crystalline resin, chloroform was used as the solvent. (2) Molecular weight measurement The following measuring equipment and analytical column were used, the eluent was passed at a flow rate of 1 mL per minute, and the column was stabilized in a thermostatic bath at 40°C. 100 μL of the sample solution was injected into the column and the measurement was performed. The molecular weight of the sample was calculated based on a calibration curve that had been prepared in advance. The calibration curve used here included several types of monodisperse polystyrene "A-500" (5.0 × 10 2 ), "A-1000" (1.01 x 10 3 ), "A-2500" (2.63×10 3 ), "A-5000" (5.97 x 10 3 ), "F-1" (1.02 x 104 ), "F-2" (1.81 x 10 4 ), "F-4" (3.97 x 10 4 ), "F-10" (9.64×10 4 ), "F-20" (1.90×10 5 ), "F-40" (4.27×10 5 ), "F-80" (7.06×10 5 ), "F-128" (1.09×10 6 ) (all manufactured by Tosoh Corporation) were used as standard samples. The numbers in parentheses indicate the molecular weight. When the samples were toner binder resins, comparative toner binder resins, and amorphous polyester resins, tetrahydrofuran was used as the eluent, and when the samples were crystalline resins, chloroform was used as the eluent. Measuring device: "HLC-8220GPC" (Tosoh Corporation) Analytical column: "GMHXL+G3000HXL" (manufactured by Tosoh Corporation)
[0127] [Softening point of resin] Using a flow tester "CFT-500D" (Shimadzu Corporation), 1 g of sample was heated at a temperature increase rate of 6°C / min, while applying a load of 1.96 MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1 mm and a length of 1 mm. The plunger descent amount of the flow tester was plotted against the temperature, and the temperature at which half of the sample flowed out was taken as the softening point.
[0128] [Glass Transition Temperatures of Toner Binder Resins, Comparative Toner Binder Resins, and Amorphous Polyester Resins] Using a differential scanning calorimeter "Q-20" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of sample was weighed into an aluminum pan, heated to 200°C, and cooled to 0°C at a rate of 10°C / min. The sample was then heated at a rate of 10°C / min, and the glass transition temperature was determined as the temperature at the intersection of the extension of the baseline below the highest endothermic peak temperature and the tangent line showing the maximum slope from the rising part of the peak to the top of the peak.
[0129] [Resin Crystallinity Index] Using a differential scanning calorimeter "Q-20" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of sample was weighed into an aluminum pan and cooled from room temperature (20 ° C) to 0 ° C at a temperature drop rate of 10 ° C / min. The sample was kept at 0 ° C for 1 minute, and then heated to 180 ° C at a temperature increase rate of 10 ° C / min, and the calorific value was measured. The temperature of the largest peak among the observed endothermic peaks was taken as the maximum endothermic peak temperature. The crystallinity index of the resin was calculated from the ratio of the softening point of the resin measured by the above method to the maximum endothermic peak temperature (softening point ( ° C) / maximum endothermic peak temperature ( ° C)).
[0130] [Melting point of crystalline polyester resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of sample was weighed into an aluminum pan, cooled from room temperature to -10°C at a rate of 10°C / min, and held at that temperature for 1 minute. The sample was then heated to 200°C at a rate of 10°C / min, and cooled from that temperature to -30°C at a rate of 10°C / min. The sample was then heated at a rate of 10°C / min, and the highest endothermic peak temperature observed was taken as the melting point.
[0131] [Melting point of release agent] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and then cooled from 200°C to 0°C at a rate of 10°C / min. The sample was then heated at a rate of 10°C / min and the calorific value was measured. The maximum endothermic peak temperature obtained was taken as the melting point.
[0132] [Volume median particle size of toner particles (D 50 )〕 The volume median particle size of toner particles (D 50 ) was measured as follows. Measurement device: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Coulter Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Dispersion liquid: "EMULGEN (registered trademark) 109P" (polyoxyethylene lauryl ether, manufactured by Kao Corporation, HLB (hydrophile-lipophile balance, Griffin method) = 13.6) was dissolved in the electrolyte to adjust the concentration to 5% by mass. Dispersion conditions: 10 mg of the measurement sample was added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser "ASU-2" (manufactured by AS ONE Corporation). Then, 25 mL of electrolyte was added, and the mixture was further dispersed for 1 minute using the ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: In a beaker, the sample dispersion is added to 100 mL of the electrolyte to adjust the concentration so that the particle diameters of 30,000 particles can be measured in 20 seconds. Then, 30,000 particles are measured, and the volume median particle diameter (D 50 ) was sought.
[0133] [Evaluation method] [Abrasion resistance] Each toner was loaded onto a copier "AR-505" (manufactured by Sharp Corporation), and a solid image was removed before passing through the fixing machine to obtain a printout in an unfixed state (print area: 2 cm × 12 cm, adhesion amount: 0.5 mg / cm 2 In addition, unfused images were printed twice on the same paper, with a layer thickness of 1.5 mg / cm 2 The unfixed image thus obtained was fixed at 180° C. at 300 mm / sec to obtain a print. The resulting print was placed on a stainless steel weight (contact area 9 cm) measuring 3 cm x 3 cm x 6.5 cm and weighing 500 g. 2 ) was placed on the surface and moved back and forth over the print at a speed of 0.5 m / s. One round trip was counted as one pass, with a maximum of 50 passes. The number of passes at which black bands of toner appeared on the non-printed areas was visually confirmed to evaluate the abrasion resistance. A higher number of passes indicates better abrasion resistance.
[0134] [Resin manufacturing] <Production of binder resin for toner> Production Example 1 (Production of Resin AL-1) 4900g of propylene oxide (2.2) adduct of bisphenol A as an alcohol component, 1859g of terephthalic acid as a carboxylic acid component, 191g of silicone "KF-864" (manufactured by Shin-Etsu Chemical Co., Ltd., weight average molecular weight 30,000, kinematic viscosity 1,700 (25 ° C), functional group equivalent 3,800 g / mol) as an amine-modified silicone, 33.8g of di (2-ethylhexanoate) tin (II) as an esterification catalyst, and 3.38g of gallic acid monohydrate as an esterification promoter were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a fractionation column, a dehydration tube, a cooling tube, and a nitrogen inlet tube, and the mixture was heated to 235 ° C in a mantle heater while stirring in a nitrogen atmosphere, and reacted at normal pressure for 4.5 hours. After that, it was cooled to 190 ° C at normal pressure, and 506.9g of ion-exchanged water was added dropwise over 1 hour. The mixture was then cooled to 185° C., and the reaction was continued until the desired softening point was reached while dehydrating at 8 kPa to obtain Resin AL-1. Various physical properties were measured and are shown in Table 1.
[0135] Production Example 2 (Production of Resin AL-2) 2450 g of propylene oxide (2.2) adduct of bisphenol A and 2275 g of ethylene oxide (2.2) adduct of bisphenol A as alcohol components, 1952 g of terephthalic acid as carboxylic acid component, 188 g of silicone "KF-864" (manufactured by Shin-Etsu Chemical Co., Ltd., weight average molecular weight 30,000, dynamic viscosity 1,700 (25°C), functional group equivalent 3,800 g / mol) as amine-modified silicone, 33.4 g of tin (II) di(2-ethylhexanoate) as esterification catalyst, and 3.34 g of gallic acid monohydrate as esterification promoter were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a fractionating column, a dehydration tube, a cooling tube, and a nitrogen inlet tube, and the mixture was heated to 220°C in a mantle heater while stirring in a nitrogen atmosphere, and reacted for 7 hours at normal pressure. After that, it was cooled to 190°C under normal pressure, and 500.8g of ion-exchanged water was added dropwise over 1 hour. After that, it was cooled to 185°C, and the reaction was further carried out to the desired softening point while dehydrating at 8kPa, to obtain Resin AL-2. Various physical properties were measured and are shown in Table 1.
[0136] Production Example 3 [Production of Resin AL-3] 2450g of propylene oxide (2.2) adduct of bisphenol A and 2275g of ethylene oxide (2.2) adduct of bisphenol A as alcohol components, 1836g of terephthalic acid as carboxylic acid components, 185g of silicone "KF-864" (manufactured by Shin-Etsu Chemical Co., Ltd.) as amine-modified silicone, 32.8g of tin (II) di(2-ethylhexanoate) as esterification catalyst, and 3.28g of gallic acid monohydrate as esterification promoter were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a fractionation column, a dehydration tube, a cooling tube, and a nitrogen inlet tube, and the mixture was heated to 225°C in a mantle heater while stirring in a nitrogen atmosphere, and reacted at normal pressure for 4 hours. After that, the mixture was cooled to 190°C at normal pressure, and 492.1g of ion-exchanged water was added dropwise over 1 hour. The mixture was then cooled to 185° C. and dehydrated at 8 kPa while reacting until it reached the desired softening point, yielding Resin AL-3. Various physical properties were measured and are shown in Table 1.
[0137] Production Examples 4 and 5 [Resins AL-4 and AL-5] Resins AL-4 and AL-5 were obtained in the same manner as in Production Example 3, except that the raw material composition was changed as shown in Table 1. Various physical properties were measured and are shown in Table 1.
[0138] [Table 1]
[0139] <Production of Comparative Toner Binder Resin> Production Example 6 [Production of Resin AX-1] 4900g of propylene oxide (2.2) adduct of bisphenol A as an alcohol component, 1882g of terephthalic acid as a carboxylic acid component, 33.9g of tin(II) di(2-ethylhexanoate) as an esterification catalyst, and 3.39g of gallic acid monohydrate as an esterification promoter were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a fractionation column, a dehydration tube, a cooling tube, and a nitrogen inlet tube, and the temperature was raised to 235°C in a mantle heater in a nitrogen atmosphere and reacted at normal pressure for 6 hours, and then reacted at 10kPa until the desired softening point was obtained, obtaining resin AX-1. Various physical properties were measured and are shown in Table 2.
[0140] Production Example 7 [Production of Resin AX-2] 2450g of propylene oxide (2.2) adduct of bisphenol A and 2275g of ethylene oxide (2.2) adduct of bisphenol A as alcohol components, 1952g of terephthalic acid as carboxylic acid component, 33.4g of tin (II) di(2-ethylhexanoate) as esterification catalyst, and 3.34g of gallic acid monohydrate as esterification promoter were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a fractionation column, a dehydration tube, a cooling tube, and a nitrogen inlet tube, and the mixture was heated to 235°C in a mantle heater while stirring in a nitrogen atmosphere, and reacted at normal pressure for 3 hours, and then reacted at 10kPa until the desired softening point was obtained, to obtain resin AX-2. Various physical properties were measured and are shown in Table 2.
[0141] Production Example 8 [Production of Resin AX-3] 2450g of propylene oxide (2.2) adduct of bisphenol A and 2275g of ethylene oxide (2.2) adduct of bisphenol A as alcohol components, 1952g of terephthalic acid as carboxylic acid component, 313g of silicone "KF-864" (manufactured by Shin-Etsu Chemical Co., Ltd.) as amine-modified silicone, 33.4g of tin (II) di(2-ethylhexanoate) as esterification catalyst, and 3.34g of gallic acid monohydrate as esterification promoter were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a fractionating column, a dehydration tube, a cooling tube, and a nitrogen inlet tube, and the mixture was heated to 235°C in a mantle heater while stirring in a nitrogen atmosphere, and reacted at normal pressure for 3 hours, and then reacted at 10 kPa until the desired softening point was obtained, to obtain resin AX-3. Various physical properties were measured and are shown in Table 2.
[0142] Production Example 9 [Production of Resin AX-4] Resin AX-4 was obtained in the same manner as in Production Example 8, except that the raw material composition was changed as shown in Table 2. Various physical properties were measured and are shown in Table 2.
[0143] [Table 2]
[0144] As shown in Table 1, the toner binder resins (resins AL-1 to AL-5) produced by the production method of the present invention had a reduced VOC content compared to the comparative toner binder resins (resins AX-3 and AX-4) containing modified silicone produced by a conventional method. Surprisingly, the VOC content of resins AL-1 to AL-5 was lower than that of the comparative toner binder resins (resins AX-1 and AX-2) not containing modified silicone. This is believed to be because the VOC derived from the raw materials was removed by the production method of the present invention.
[0145] <Production of amorphous polyester resin> Production Example 10 [Production of Resin AH-1] 2450g of propylene oxide (2.2) adduct of bisphenol A and 2275g of ethylene oxide (2.2) adduct of bisphenol A as alcohol components, 1322g of terephthalic acid and 188g of dodecenyl succinic anhydride as carboxylic acid components, 20.4g of di(2-ethylhexanoate)tin (II) as esterification catalyst, and 2.04g of gallic acid monohydrate as esterification promoter were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a fractionating column, a dehydration tube, a cooling tube, and a nitrogen inlet tube, and the mixture was heated to 235°C in a mantle heater while stirring in a nitrogen atmosphere, and reacted at normal pressure for 2.5 hours, and then reacted at reduced pressure of 8kPa for 1 hour. After that, the mixture was cooled to 190°C at normal pressure, and 554g of trimellitic anhydride was added, and the temperature was raised stepwise to 210°C at a rate of 10°C / h. The reaction was then continued at 8 kPa until the desired softening point was reached, yielding Resin AH-1. Various physical properties were measured and are shown in Table 3.
[0146] [Table 3]
[0147] <Production of Crystalline Polyester Resin> Production Example 11 [Production of Resin C-1] 1,6-hexanediol (1652g) as an alcohol component, dodecanedioic acid (3123g) and stearic acid (119g) as carboxylic acid components, and di(2-ethylhexanoate)tin (II) (24.5g) as an esterification catalyst were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a fractionating column, a dehydration tube, a cooling tube, and a nitrogen inlet tube, and the mixture was heated to 140°C in a mantle heater while stirring in a nitrogen atmosphere, and reacted at normal pressure for 5 hours, and then heated stepwise to 200°C at a rate of 10°C / h. The reaction was then continued at 8kPa until the desired softening point, and resin C-1, a crystalline polyester resin, was obtained. Various physical properties were measured and shown in Table 4.
[0148] [Table 4]
[0149] [Toner manufacturing] Example 1 [Production of Toner 1] 65 parts by mass of resin AL-1, 35 parts by mass of resin AH-1, 5 parts by mass of resin C-1, 1 part by mass of negatively charged charge control agent "Bontron E-81" (manufactured by Orient Chemical Industry Co., Ltd.), 10 parts by mass of colorant "Cyanine Blue 4927" (manufactured by Dainichi Seika Chemical Industry Co., Ltd., CI Pigment Blue 15:3 (PB 15:3)), and 1 part by mass of release agent "HNP-9" (manufactured by Nippon Seiro Co., Ltd., paraffin wax, melting point: 80°C) were thoroughly mixed in a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.), and then melt-kneaded using a co-rotating twin-screw extruder (PCM-30, manufactured by Ikegai Co., Ltd.) at a screw rotation speed of 200 r / min and a barrel setting temperature of 100°C. The resulting melt-kneaded product was cooled and classified using an IDS pulverizer / classifier (manufactured by Nippon Pneumatic Co., Ltd.) to determine the volume median particle size (D 50 ) was 8 μm. 1 part by mass of external additive "AEROSIL NAX 50" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic silica, hydrophobic treatment agent: HMDS, number average particle diameter: approximately 30 nm) was added to 100 parts by mass of the obtained toner particles, and the mixture was mixed in a Henschel mixer at 3,600 r / min for 5 minutes to perform external additive treatment, thereby obtaining Toner 1. The abrasion resistance was measured and is shown in Table 5.
[0150] Examples 2 to 5 and Comparative Examples 1 to 4 [Toners 2 to 5, and 51 to 54] Toners 2 to 5 and 51 to 54 of Examples 2 to 5 and Comparative Examples 1 to 4 were obtained in the same manner as in Example 1, except that the resin was changed as shown in Table 5. The abrasion resistance was measured and is shown in Table 5.
[0151] [Table 5]
[0152] From the results of the above-mentioned Examples and Comparative Examples, it is clear that according to the present invention, a toner binder resin having a low VOC content can be obtained, and further, a toner for developing electrostatic images containing the toner binder resin has excellent abrasion resistance.
Claims
1. A method for producing a binder resin for toner, which is a reaction product of an alcohol component containing a dihydric or higher alcohol, a carboxylic acid component containing a dihydric or higher carboxylic acid compound, and a modified silicone, and which has a toluene-equivalent content of volatile organic compounds containing cyclic siloxanes that volatilize when heated at 120° C. for 60 minutes of 10 mg / kg or less, Step 1: A step of condensing the alcohol component, the carboxylic acid component, and the modified silicone to obtain a reaction mixture containing a cyclic siloxane; Step 2: steam distilling the reaction mixture; and Step 3: Removing water by reducing pressure and further condensing the reaction mixture; A method for producing a binder resin for toner comprising the steps of:
2. The method for producing a binder resin for toner according to claim 1 , wherein the condensation in the step 1 is carried out at a temperature of 200° C. or higher and 235° C. or lower.
3. The method for producing a binder resin for toner according to claim 1 or 2, wherein the steam distillation in the step 2 is carried out at a temperature of 180° C. or higher and 200° C. or lower.
4. The method for producing a binder resin for toner according to any one of claims 1 to 3, wherein the condensation in the step 3 is carried out at 180°C or higher and 200°C or lower and at 3 kPa or higher and 70 kPa or lower.
5. 5. The method for producing a binder resin for toner according to claim 1, wherein the modified silicone is a modified silicone having at least one group selected from the group consisting of an amino group, a carboxy group, an epoxy group, and a carbinol group.
Citation Information
Patent Citations
Toner binder resin
JP2020063412A
White toner
JP2020190648A